Avaliação da vibração das pregas vocais e inteligibilidade de fala sob a influência de diferentes características acústicas de salas de aula - Alessandra Terra Vasconcelos Rabelo (2015)
Aim: The main objective of this study wasto evaluate speech intelligibility and the vibration of vocal folds in order to assess the relationship with the acoustical characteristics of classrooms. Method: Cross-sectional study with analysis of students performance on tests of intelligibility and vocal production of teachers in 18 classrooms in nine public schools in the city of Belo Horizonte and evaluation of 30 women aged between 22 and 50 years. The acoustic parameters equivalent sound pressure level (Leq), reverberation time (T30) and STI (Speech transmisson index) were measured. A speech intelligibility test was performed with 273 students, 45.4% of whom were male, in 9 of the evaluated schools, with an average student age of 9.4 years. The results of the speech intelligibility test were compared to the values of the acoustic parameters by a t-test. The analysis of the use of the voice was performed with and without the presence of noise in the classroom to check the dose parameters, fundamental frequency, voice level, percentage of speech and phonation time. The sample of women to voice assessment consisted of 30 women aged between 22 and 50 years. The vocal VoxLog meter was used in the two-hour period, for data collection. It consists of a microphone, an accelerometer fixed on the participant's neck and a portable unit that stores the data phonation. Results: The background noise (L90) varied from 45.6dB(A) to 64.3dB(A). The Leq value of empty and furnished classrooms varied from 54.5dB(A) to 70.4dB(A). The reverberation time, based on the average frequencies of 500, 1.000, and 2.000 Hz, varied from 0.69s to 2.09s. The STI varied from 0.47 to 0.70. Children demonstrated better results in speech intelligibility tests conducted in classrooms with less noise, a lower reverberation time, and larger STI values. These associations were all statistically significant (p<0.05). Vocal parameters of dose, fundamental frequency, voice level, percentage of speech and phonation time had their values increased with the presence of noise. Conclusion: The majority of classrooms do not meet the recommended regulatory standards for good acoustic performance. Acoustic parameters have a direct influence on the speech intelligibility of students. Noise contributes to a decrease in their understanding of orally presented information, which can lead to negative consequences for their education and their social integration as future professionals. In addition, the great vocal effort identified by the results of voice analysis show that excessive noise and inadequate acoustic conditions can have negative consequences for the vocal health of exposed individuals. New noise control measures and orientation for students and teachers in terms of decreasing of noise present in the classrooms and take care of voice are essential. The effects of noise on voice and intelligibility were confirmed and should be avoided.